Analysis of CEPH-accredited online public health doctoral programs and MPH degree holder demand - Barbara Lewis; Francisco Sy (Frontiers in Public Health, 2023)
IntroductionThe number of doctoral programs to train future public health leaders is critical in meeting the demand of global health challenges in the 21st century. Ten United States online public health doctoral programs accept only a fraction of interested learners.MethodsThis research examines the launch of the first online public health doctoral program, accredited by the Council on Education for Public Health, and compares nine similar programs that have followed in the ensuing 12 years.ResultsSurvey results highlight the demand by Master of Public Health degree holders for online public health doctoral programs; 84.11% of survey respondents indicated an interest in obtaining a doctoral degree.DiscussionIf we strive to answer the question posed by the Institute of Medicine in 2003, “Who will keep the public healthy?” then we need to provide education that is accessible, efficient and equitable for interested learners, most of whom are turned down by online public health doctoral programs that have limited capacity.